The Role of Implied Reader in the Realm of Literary Criticism - Hossein Safi Pirlooje (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This article aims to examine the process of text reading and understanding, based on the concept of implied reader, for the definition of which, we have synthesized herein the seemingly antithetical methods of ‘authorial’ and ‘reader-oriented’ criticism. Of this definition, we have taken benefit against rhetorical hermeneutics. Adopting such an anti-objectivist approach, we have taken the text as nothing but a ground for the fusion of authorial horizon with that of the readership, and the implied reader, as a theoretical construct drawn out of rules and regulations most prevalent in story-telling and reading. The ideal reader as such does not denote any specific referent, though may duly bind different kinds of over-reading. In the end, it is concluded that by pulling together the rubrics of story reading under the cover term ‘implied reader’, the exaggerated discordance usually held between intentionalist and reader-response critics would be resolved in favor of an explication more attentive to the synergistic nature of meaning assignment to a text.